El mal de ojo y su relación con el marasmo y kwashiorkor: El caso de las madres de Turbo, Antioquia, Colombia (2007)
ABSTRACT: To describe perceptions and sociocultural practices by the mothers facing severe malnutrition in children: Marasmus and Kwashiorkor. Methodology: Descriptive ethnography. Twenty semi-structured interviews and two tribal ones were carried. Homes and hospitalized children were observed. Analysis was manually performed. Results: Mother perceives severe malnutrition like “mal de ojo” consequence afflicting children under seven. Mal de ojo is classified as “drying-eye” or as “street-eye”. Mothers think that “drying-eye” emaciates children meaning something like what we call marasmus, where as we cannot tell weather “street-eye” means kwashiorkor; but in any case kwashiorkor is deemed to be caused by mal de ojo. “Traditional” medics like rezanderos perform important tasks in the treatment of cultural linked illnesses. Conclusions: Malnourishment is considered a “state” and finally it is reduced to statistical data hindering the integral treatment of children.The study reveals a world unknown by the biomedical system and a world of cultural practices facing malnourishment that adequately assessed could improve integral treatment and prevent infant mortality by severe malnourishment or by mal de ojo.